Determinan Faktor-Faktor yang Mempengaruhi Komitmen dan Kemampuan Keluarga dalam Mencegah Stunting pada Baduta: Determinants Affecting Family Commitment and Capability in Preventing Stunting in Children Under Two Years - Taufiqurrahman, Taufiqurrahman; Hatijah, Nur; Intiyati, Ani (Amerta Nutrition, 2024)
Background: Stunting remains a public health issue in Indonesia. Despite a decline in national prevalence, East Java recorded a stunting prevalence of 32.7%, exceeding national standards and those set by the World Health Organization (WHO). Objectives: This study aimed to identify the factors influencing family commitment and capability in preventing stunting in children under two years old. Methods: The study employed an observational survey design involving 150 mothers of children aged 0–2 years in the Puskesmas (Community Health Center) areas of Surabaya. Data were collected using questionnaires to assess personal, interpersonal, cognitive-behavioral, resource, and fundamental family value variables. Analysis was conducted using Structural Equation Modeling (SEM) with Partial Least Square (PLS) methodology. Results: Personal, interpersonal, and cognitive-behavioral factors significantly influenced family commitment to stunting prevention. Approximately 89.89% of a family’s ability to monitor child growth and development could be predicted by the study model. However, resource factors and fundamental family values were not significant. Conclusions: Interpersonal, cognitive-behavioral factors, and family assessment can increase family commitment in preventing stunting in children under two years. Assistance from health workers is essential to further strengthen family commitment to stunting prevention.